The impact of the manager–shareholder conflict on acquiring bank returns - Cornett, Marcia Millon; Hovakimian, Gayane; Palia, Darius; Tehranian, Hassan (Journal of Banking & Finance, 2003)
This paper examines whether shareholder value-maximizing corporate governance mechanisms assist in reducing the managerial incentive to enter value-destroying bank acquisitions. We find that diversifying bank acquisitions earn significantly negative announcement period abnormal returns (AR) for bidder banks whereas focusing acquisitions earn zero AR. We then find that corporate governance variables (such as CEO share and option ownership and a smaller board size) in the bidding bank are less effective in diversifying acquisitions than in focusing acquisitions. These results are robust to the inclusion of the usual control variables.